2016
DOI: 10.1002/jcb.25804
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of the Pioneer Transcription Factor FoxA1 Promotes Activation of Estrogen Signaling

Abstract: The pioneer transcription factor FoxA1 plays an important role in estrogen signaling by opening closed chromatin and promoting recruitment of the estrogen receptor to its target regions in DNA. In this study, we analyzed tyrosine phosphorylation of FoxA1 by the non-receptor-type tyrosine kinase c-Abl. c-Abl was shown to phosphorylate FoxA1 at multiple sites, especially in the N- and C-terminal regions. Tyr429 and Tyr464 were identified as the major phosphorylation sites in the FoxA1 C-terminal region. The phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…9) Tyrosine phosphorylation in the C-terminal region of FOXA1 was shown to enhance this chromatin remodeling activity. 10) Because estrogen receptor-α (ERα) depends on this chromatin remodeling activity, FOXA1 is crucial for the development of not only normal mammary gland but also estrogen-dependent breast cancer. 11,12) Recent studies have shown that FOXA1 suppresses EMT progression in pancreatic and prostate cancer.…”
mentioning
confidence: 99%
“…9) Tyrosine phosphorylation in the C-terminal region of FOXA1 was shown to enhance this chromatin remodeling activity. 10) Because estrogen receptor-α (ERα) depends on this chromatin remodeling activity, FOXA1 is crucial for the development of not only normal mammary gland but also estrogen-dependent breast cancer. 11,12) Recent studies have shown that FOXA1 suppresses EMT progression in pancreatic and prostate cancer.…”
mentioning
confidence: 99%
“…The mechanism of Src-mediated suppression of apoptosis through Src substrates still remains poorly understood, possibly because protein-tyrosine phosphorylation is extremely unstable within cells. We, therefore, assume that phosphorylation levels of substrates are very rapidly regulated by a balance of the activities between tyrosine kinases and tyrosine phosphatases, like ON/OFF switching in a microprocessor (5,(22)(23)(24)(25)(26)(27)57). Nonetheless, carefully using a high dose of the potent tyrosine phosphatase inhibitor Na 3 VO 4 , we are able to detect tyrosine phosphorylation of endogenous proteins and have shown the significance of tyrosine-phosphorylated substrates (5,24,26,27).…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, assume that phosphorylation levels of substrates are very rapidly regulated by a balance of the activities between tyrosine kinases and tyrosine phosphatases, like ON/OFF switching in a microprocessor (5,(22)(23)(24)(25)(26)(27)57). Nonetheless, carefully using a high dose of the potent tyrosine phosphatase inhibitor Na 3 VO 4 , we are able to detect tyrosine phosphorylation of endogenous proteins and have shown the significance of tyrosine-phosphorylated substrates (5,24,26,27). Because we have learned from our own experiences that the inhibitory potency of Na 3 VO 4 , albeit an inorganic compound, against the activity of protein-tyrosine phosphatases is drastically lost (i) at neutral pH and (ii) by freeze-thawing, we dissolve Na 3 VO 4 in H 2 O just before use or store a Na 3 VO 4 stock solution in single-use aliquots at Ϫ20°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional treatment example from this decade involves the use of "Imatinib"®, which is "a designer drug" used in the treatment of multiple cancers, most notably Philadelphia chromosomepositive (Ph+) chronic myelogenous leukemia. This drug has been designed, based upon insight into the disease's molecular pathology, with a certain degree of precision (Yamaguchi et al, 2016).…”
Section: The Medical Implications Of Rds Behaviorsmentioning
confidence: 99%